Identifikasi jumlah angka kuman pada dispenser metode TPC (Total Plate Count) - Zuriani Rizki; Fitriana Fitriana; Asri Jumadewi (Politeknik Kesehatan Kemenkes Aceh, 2022)
Background: Food contamination can be caused by various factors, including food handler knowledge, body hygiene, food sanitation, and the cleanliness of cutlery. A microbiological examination that can be done is a swab of cooking utensils and cutlery, including a germ count examination. The dispenser is one of the tableware widely used by the community to provide drinks. The use of dispensers in gallon bottled drinking water consumers makes serving drinking water practical, but dispenser cleanliness is generally less considered by consumers.Objectives: The study aims to determine the number of germs in standard-temperature water faucets and hot-temperature water faucet dispensers using the TPC (Total Plate Count) method.Methods: This type of research is explanatory through a descriptive-analytic approach. The research was conducted at the Medical Technology Laboratory in 2022. Samples were taken from five water depot managers in Banda Aceh City. The media and reagents used were Physiological NaCl (0,85%), Aquadest, and Nutrient Agar (NA) media. Statistical analysis using Independent T-test at 95% CI.Results: The normal-temperature water faucet showed the highest number of germs, 193 colonies/cm2, and the lowest number of germs was shown by the hot-temperature water faucet (23 colonies/cm2). There was a difference in the number of germs between standard water taps and hot water taps (p= 0,025) in several dispensers in Banda Aceh City.Conclusion: There is a significant difference in the number of germs from dispenser swabs between standard-temperature water faucets and hot water faucets.